Faktor-faktor yang mempengaruhi Tax Avoidance: Sales Growth, Profitabilitas dan CSR - Juli Ratnawati; Vita Resti Wulidasani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This studies is performed to observe sales increase,profitability,and  corporate  social  duty as variables that affect  tax  avoidance  practices.  The  populace  of  this studies is the  mining  area  which  is listed on Indonesia  stock  market  in  period  of  2019-2021.  The  usage  of  a purposive sampling  approach. The secondary facts  obtained  from Indonesia  stock  market  and  economic  record  of  every  employer  that  applicable  with purposive sampling  standards . Speculation  testing  makes use of  multiple  linear  regression  evaluation  with  the  help  of  SPSS  software   program. The  consequences  of   this  studies  display  that  sales  increase  has  an  effect on  Tax   Avoidance.  Profitability  does  no  longer   affect   Tax  Avoidance.  CSR  impacts  Tax  Avoidance.